2006
DOI: 10.1186/1747-597x-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis, motivation, and life satisfaction in an internet sample

Abstract: Although little evidence supports cannabis-induced amotivational syndrome, sources continue to assert that the drug saps motivation [1], which may guide current prohibitions. Few studies report low motivation in chronic users; another reveals that they have higher subjective wellbeing. To assess differences in motivation and subjective wellbeing, we used a large sample (N = 487) and strict definitions of cannabis use (7 days/week) and abstinence (never). Standard statistical techniques showed no differences. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 37 publications
4
34
0
1
Order By: Relevance
“…The results showed that alcohol and cannabis abuse/dependence symptoms were significantly associated with life satisfaction, with greater numbers of symptoms being associated with lower levels of life satisfaction. This finding is consistent with previous research, which has suggested that alcohol and cannabis abuse are associated with decreased life satisfaction [3,[7][8][9][14][15][16].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results showed that alcohol and cannabis abuse/dependence symptoms were significantly associated with life satisfaction, with greater numbers of symptoms being associated with lower levels of life satisfaction. This finding is consistent with previous research, which has suggested that alcohol and cannabis abuse are associated with decreased life satisfaction [3,[7][8][9][14][15][16].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, in a cross-sectional survey of over 340 000 individuals, Strine et al [14] reported that heavy drinking was associated with lower levels of life satisfaction. Other studies have reported similar associations between cannabis use and life satisfaction [3,8,9]. For example, Zullig et al [9] found that cannabis use was significantly associated with reduced life satisfaction among high school students.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…A limitation of these results was the possibility of overlap between negative PLEs and the amotivational syndrome in cannabis users, which includes social indifference, apathy and passivity (McGlothlin & West, 1968). Despite presenting contradictory evidence (Barnwell, Earleywine, & Wilcox, 2006), possibly related to inconsistency in measurements of the substance use, the amotivational syndrome has been reported in heavy cannabis users who did not, necessarily, present a diagnosis of schizophrenia or psychotic symptoms (Bersani et al, 2016;Looby & Earleywine, 2007;Rovai et al, 2013). However, we consider that this alternative explanation for the results found in the present review is unlikely, since in most studies included in our review, moderate and light users of cannabis reported not only more negative PLEs but also more positive and depressive PLEs as compared to non-users Skinner et al, 2011;Stefanis et al, 2002;Verdoux et al, 2003;.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, symptoms of heavy use (e.g., blackouts, vomiting, paranoia) and withdrawal symptoms may be unique to alcohol or marijuana. Similarly, chronic marijuana users may exhibit some unique features such as apathy that is often considered a feature of marijuana use in the popular media, though empirical evidence for this is limited (Barnwell et al, 2006; Zimmer & Morgan, 1997). Despite similarities of consequences across alcohol and marijuana, endorsement of a symptom may indicate a different level of severity for each drug.…”
mentioning
confidence: 99%